An elementary approach to solve recursions relative to the enumeration of S-Motzkin paths. Issue 5 (4th May 2021) - Prodinger, Helmut
Abstract : S-Motzkin paths (bijective to ternary trees) and partial version of them are calculated using only elementary methods from linear algebra.